Humanity in a creative universe - Kauffman, Stuart A. (Oxford University Press, 2016)
In this fascinating read, Kauffman concludes that the development of life on earth is not entirely predictable, because no theory could ever fully account for the limitless variations of evolution. Sure to cause a stir, this book will be discussed for years to come and may even set the tone for the next "great thinker."